Five Factors Influencing the Students’ Motivation to Learn English as a Foreign Language: A Closer Look into Montessori Classroom Environment - Batubara, Febti; Derin , Tatum; Putri, Nunung Susilo; Yudar , Ratih Saltri (REiLA : Journal of Research and Innovation in Language, 2020)
Good learning environment will bring out qualified students. This study focuses on the Montessori method, which is an approach of education designed to train the students’ independence in learning. The study uses descriptive quantitative research design to describe the factors of Montessori classroom environment on the motivation of students in Royal Prime Montessori Elementary School Pekanbaru in academic year 2018/2019. The sample of study is 55 students selected from five classes. The data were collected using questionnaire and observation checklist. This study found five factors influencing the students’ motivational condition, i.e., teacher’s presence, personal attitude, Montessori materials, classroom conditions and friends’ influence. This study revealed that the students taught with this method are active and cooperative during their English learning activities.